Preparation of Chiral Stationary Phase by Dynamic Grafting BSA on the Organic-Silica Hybrid Monolithic Column Based on Schiff-Base Reaction. Issue 1 (March 2020) - Sun, Yue-Na; Li, Pan; Chen, Meng-Jiao; Lv, Yun-Kai
Abstract: The prepared hybrid monolithic column (HMC) with epoxy groups on the surface was reacted with polyethyleneimine, and then reacted with glutaraldehyde. The chiral monolithic column was prepared by dynamically grafting bovine serum albumin (BSA) onto the newly modified HMC by Schiff-base reaction. The obtained chiral monolithic column was characterized by SEM and IR. The effects of the concentration of the BSA solution, flow rate and grafting time on the grafting amount were optimized. The properties of chiral monolithic column were tested with benzoin as the chiral object. The results showed that the obtained grafting amount of BSA was 56.1 mg/g under the optimized conditions. The chiral monolithic column had homogeneous network skeleton structure and good reusability. The method of preparing chiral monolithic column had good reproducibility.